Ouverture de “Global Competition Heats Up Further” - Silvio M. Brondoni (Symphonya, 2025)
From the Russian invasion of Ukraine, a new phase of globalization has begun, developed by the world's major multinationals (China, South Korea, USA, India, etc.). A new phase which can be defined of 'wild globalization', characterized by an exasperated and boundless search for profit, to satisfy the objectives of a global finance that since the 1980s have imposed on multinationals increasing tasks of business results (Profit or Perish). In the last ten years, China, India, Vietnam and many other countries have embarked on a rapid path of globalization. Global development is increasingly alive, and in exemplifying the continuous development of global opening, we can observe how the Catholic Church, in the last ten years with Pope Bergoglio, has also changed the logic of the basic organization, assuming a global vision. In 2025, the 135 eligible Cardinal electors of the new Pope represent 71 countries on all six inhabited continents.